2008
DOI: 10.1523/jneurosci.0563-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Neuronal Differentiation of Mouse Embryonic Stem Cells after Transient Expression of Neurogenin 1 and Treatment with BDNF and GDNF:In VitroandIn VivoStudies

Abstract: Differentiation of the pluripotent neuroepithelium into neurons and glia is accomplished by the interaction of growth factors and cell-type restricted transcription factors. One approach to obtaining a particular neuronal phenotype is by recapitulating the expression of these factors in embryonic stem (ES) cells. Toward the eventual goal of auditory nerve replacement, the aim of the current investigation was to generate auditory nerve-like glutamatergic neurons from ES cells. Transient expression of Neurog1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 60 publications
8
108
0
Order By: Relevance
“…Several potential candidate cell sources including mouse embryonic stem (ES) cells [12,13], human ES-cell-derived otic progenitors [14], olfactory-derived neural stem cells (NSCs) [15], and brainderived NSCs [12,16] have been transplanted into the auditory system. In the in vitro studies, identification of spiral ganglion stem/progenitor cells has been studied using the culture methods that are similar to identifying NSCs in subventricular zone and subgranular zone.…”
mentioning
confidence: 99%
“…Several potential candidate cell sources including mouse embryonic stem (ES) cells [12,13], human ES-cell-derived otic progenitors [14], olfactory-derived neural stem cells (NSCs) [15], and brainderived NSCs [12,16] have been transplanted into the auditory system. In the in vitro studies, identification of spiral ganglion stem/progenitor cells has been studied using the culture methods that are similar to identifying NSCs in subventricular zone and subgranular zone.…”
mentioning
confidence: 99%
“…Embryonic stem cells are pluripotent cells derived from the first stage of embryonic development, containing the potential to replace tissues lost by injury (Reyes et al, 2008;Kalladka and Muir, 2014). However, due to their isolation source, the usage of ESCs presents ethical issues in medical research and as a potential therapeutic strategy (Kalladka and Muir, 2014).…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%
“…Differentiation is successfully controlled through the use of specific media and culture conditions. For example, the use of media containing fetal bovine serum and ESC supplement coincides with upregulation of TUJ1, suggesting the differentiation of ESCs to neuronal cells (Reyes et al, 2008). By tightly controlling experimental parameters and timing in conjunction with growth and inhibitory factors in media and culture conditions, ESCs can be preferentially driven toward specific cell phenotypes (Arvidsson et al, 2002).…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%
“…Toward successful replacement of damaged SGNs by ESCs, establishment of SGN-specific cell types from ESCs is important. Transient expression of Neurog1, which is expressed in developing otocysts and is required for SGN differentiation, migration and survival, and treatment with glial cell line-derived neurotrophic factor (GDNF) turned undifferentiated ESCs into auditory nerve-like glutamatergic neurons [35]. Although previous studies identified ESCs as the promising candidates as transplants, ESCbased therapy is complicated by immune rejection and ethical problems.…”
Section: Regeneration Of Spiral Ganglion Neuronsmentioning
confidence: 99%